The cytotoxic effect of pinostrobin fingerroot (boesenbergia pandurata)on the culture of hela cells - Rosmelia Rosmelia; Betty Ekawati Suryaningsih; Hady Anshory; Yohanes Widodo Wirohadidjojo (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background : Cancer is one of the leading causes of death worldwide, therefore struggles to find more effective treatment and prevention is needed. Several studies has been performed using natural ingredients, one of which is Temu Kunci (B. pandurata). Temu Kunci extract contains flavonoid pinostrobin that has been showed as having cytotoxicity effects. Cytotoxicity tests of pinostrobin have been performed on several tumor cell lines, but its cytotoxicity effect on HeLa cell line has never been reported. Objective : To assess cytotoxicity effect of pinostrobin temu kunci on HeLa cell culture Methods : This study used simple experimental design. Pinostrobin were isolated from temu kunci and proved by TLC densitometry compared to standard pinostrobin. HeLa cell culture were treated with pinostrobin with concentrations 5, 25, 50, 75, 100, and 250 ug/mL. Cytotoxicity test were performed by MTT assay. Data were analyzed using one-way ANOVA. Results : There was significant difference (p=0.000) of means of cell viability percentage, respectively: 92.58 ± 9.84 (5μg/mL), 91.78 ± 4.4 (25μg/mL), 80.09 ± 4.51 (50μg/mL), 76.89 ± 7.75 (75μg/mL), 67.85 ± 11.31 (100μg/mL), dan 48.82 ± 16.61 (250μg/mL). The IC50 was 250μg/mL. Conclusion : Pinostrobin showed no active cytotoxicity effect on HeLa cell culture.